DMSO-Mediated Synthesis of Methylene-Bridged Unsymmetrical Bisamides in the Presence of AcOH - Zhang, Yi; Zhou, Dongheng; Ma, Yongmin; Chen, Jing (Synthesis, 2020)
A simple and efficient procedure for the synthesis of N-[(methylthio)methyl]benzamides and methylene-bridged unsymmetrical bisamides was achieved mediated by DMSO in the presence of acetic acid. DMSO plays a dual role in the transformation, as not only a solvent, but also an environmentally benign methylene source. The protocol provides new strategies for effective synthesis of unsymmetrical bisamides and avoids the use of transition-metal catalysts.
Keywords: unsymmetrical bisamide; DMSO; AcOH; amide